Photosynthetic response curve of grafted and non-grafted Japanese cucumber plants in relation to irradiance - Amaro, A. C.E. [UNESP]; Macedo, A. C. [UNESP]; Goto, R. [UNESP]; Ono, E. O. [UNESP]; Rodrigues, J. D. [UNESP] (International Society for Horticultural Science (ISHS), 2019)
Photosynthesis is directly proportional to light and the stomatal aperture reduces with the decrease in irradiance. The increase in irradiance reduces the respiration and photorespiration, besides increasing CO2 fixation. As grafting induces significant changes in the growth and development of the plant, the present work aimed to evaluate the response curve of the CO2 assimilation rate, as a function of PPFD (photosynthetic photon flux density) in grafted and non-grafted Japanese cucumber plants (Cucumis sativus L.). The study was performed in an experimental area of the FCA, UNESP, Botucatu-SP, Brazil, in greenhouse conditions. The response curve was obtained with the IRGA LI6400, reducing the PPFD of 2000 to 0 µmol m-2 s-1 at intervals of 300 µmol m-2 s-1 until 100 µmol m-2 s-1, after which it was used at intervals of 50 µmol m-2 s-1, 42 days after transplant, using four replicates of each type of plant. It was observed that in grafted plants the light compensation point was higher than in non-grafted ones (58.65 and 32.24 µmol m-2 s-1, respectively), indicating that grafted plants require a higher amount of light than non-grafted plants to submit similar CO2 assimilation. Non-grafted plants showed a saturation tendency of photosynthesis by light in PPFD values above 1200 µmol m-2 s-1, whereas the grafted plants showed it above 1500 µmol m-2 s-1. These results indicated that grafting affected photosynthetic metabolism, and so the non-grafted plants have lower light compensation point and saturation point of photosynthesis by light than grafted plants. This suggests that grafted plants tend to tolerate higher radiance levels than non-grafted plants.
Keywords: Cucumis sativus L; Gas exchange; Grafting; Light; Photosynthesis